Avaliação da confiabilidade da ferramenta global trigger tool do institute for healthcare improvement para estimativa da ocorrência de eventos adversos em pacientes adultos internados em um hospital público de belo horizonte - Sara Monteiro de Moraes (2018)
Introduction: Patient safety is a fundamental principle of care and a critical component in providing quality health assistance. Its improvement depends on the ability to understand the frequency of occurrence and types of adverse events, in order to prioritize actions to improve the structure of the care system. For this, valid, reproducible, cost-effective and applicable measurement strategies are needed in different contexts of care settings and resource availability. Among the traditionally used methods are voluntary reporting, direct observation, and retrospective hartreview. In 2003, the Institute for Healthcare Improvement developed the lobal Trigger Tool (GTT-IHI), a variation on the methodology of etrospective chart review based on the search for triggers which roposes the estimation of the occurrence of adverse events by a simple, cheap nd easy to execute method. In Brazil, some institutions adopt it as one of the strategies for risk management, however, no studies were found that evaluated its validity and reliability. Objectives: To adapt the GTTIHI for use in a public hospital in Brazil, to evaluate the reliability of the test and to compare the performance of nurses and medical students as primary reviewers. Methods: The research was carried out in a large, public and teaching hospital, located in the city of Belo Horizonte, Minas Gerais. Based on a Portuguese translation of the GTT-IHI provided by a Brazilian organization that already used the tool, small adaptations were made regarding terms and drugs most frequently used in the institution where the study would be carried out. A team of trained reviewers, consisting of four primary reviewers - two medical academics and two experiencednurses - and two medical reviewers, applied the tool in a random sample of 220 hospitalizations occurred in October 2016. Reliability among reviewers was assessed per inter-examiner agreement and Kappa coefficient for the following combinations of reviewers: academic-academic, nurse-nurse, academic pair-nurse pair, academicpair-doctor, and nurse pair-doctor. The outcomes of interest were identification of the adverse event and its level of severity of harm. The data were analyzed considering as units of study: (1) hospitalization; (2) all possibilities of agreement (identification of each event individually added to hospitalizations without events). Results: 199 adverse events were identified in 90 hospitalizations (40.9% of admissions had atleast one adverse event), with rates of 76.1 adverse events per 1,000 patient-days and 90.5 adverse events per 100 admissions. Kappa (K) values differed substantially between the two study units employed and the two outcomes studied, with better results for identification of adverse events using the study unit hospitalization (K 0.41 - 0.76) and for classification of the severity of the harm using the unit of study allpossibilities of agreement (K 0,43 - 0,77). There was no significant difference between the performance of the academic pair and the nurse pair as primary reviewers in any of the analyses. Conclusion: Data on adverse event rates and method reliability found in this study are similar to those of published in international studies that used the same methodology. The GTT-IHI showed moderate inter-rater reliability. This evidence on the reproducibility of the method is an important step ininvestigating the utility of the instrument to generate data and indicators of patient safety and quality of care at the local level in the context of Brazilian public hospitals. The study also suggests that the reliability of the method does not differ when medical students or nurses perform the primary review of events